Sewage sludge treatment by membrane anaerobic system (MAS) - Musliha, Mohamed (2010)
The performance of Membrane Anaerobic System (MAS) was investigated in treating raw sewage sludge. Certain parameters were investigated such as Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solid (TSS) and pH. MAS consist of Ultrafiltration membrane for solid-liquid separation with 1.5 – 2.0 bar of operational pressure. An enrichment culture of methanogenic bacteria was developed in the digester when seed sludge was feed into 50 L digester. The raw sewage sludge was obtained from the Indah Water Municipal Treatment Plant at Taman Seri Mahkota Aman KUN 112. The digester operates 5 hours per day for 11 days. The conventional method to treat raw sewage sludge is by using Aerobic and Anaerobic digestion. Aerobic digestion is expensive method since it used oxygen and anaerobic digestion required large area and slower process. As an alternative method, MAS was being invented and offer great advantages. In this study, 70 % of methane gas was produce and removal efficiency of COD was up 60.74% to 97.24%.MAS treatment efficiency is greatly affected by pH, temperature, organic loading rate (OLR) and hydraulic retention time (HRT).MAS was found to be the biological treatment system to achieve a high COD removal in a short period of time and the effluent colour is more clear. Thus make MAS is a good alternative for treating wastewater.